Flexural behavior of engineered cementitious composite (ECC) slabs with polyvinyl alcohol fibers - Said, S.H.; Razak, Hashim Abdul; Othman, I. (Elsevier, 2015)
This paper investigates the effects of polyvinyl alcohol (PVA) fibers on the toughness, compressive and flexural strength of engineered cementitious composite (ECC) cubes and slabs. The key parameter discussed in this study is the reinforcing index. To evaluate the strain-hardening behavior of ECC with different PVA fiber contents, tests were conducted in direct tension. Flexural toughness was also evaluated following ASTM C 1018 procedure and post-cracking strength technique (PCSm). Results showed that the compressive strength decreases as the reinforcing index increases in a nonlinear trend. By increasing the reinforcing index, the first crack load decreases and ultimate strength slightly increases. Furthermore, a significant increase in the first crack strength was obtained by an excess value 1000 of the reinforcing index. There is a significant increase in the deflection at ultimate load and the deflection at failure as the reinforcing index increases in a linear manner. The strain-hardening and multiple cracking behavior were observed for slabs with reinforcing indices higher than 316 whereas the softening behavior was observed for lesser values. The ECC PVA slabs did not attain the desired ductility due to the rupture of PVA fibers. A significant increase has occurred to the toughness indices I-20, I-30 and I-40 with the increase in reinforcing index. Moreover, the indices exceed the limitations considered. A new definition as an extension to the definition given in ASTM C 1018 was proposed for ECC PVA material according to the observed results. All the residual strength factors increased as the reinforcing index increases which indicates a higher amount of strength retained. The PCS60 values increased with increase in the reinforcing indices. Thus, the increase in PCS60 values indicates higher flexural performance, better ductility and energy absorption capacity for slabs. (C) 2014 Elsevier Ltd. All rights reserved.